PEMANFAATAN MUSIC STYLE SEBAGAI MEDIA PEMBELAJARAN KEYBOARD DALAM KEGIATAN EKSTRAKURIKULER MUSIK DI SD NEGERI 1 KALIPUCANG WETAN KECAMATAN WELAHAN KABUPATEN JEPARA - novaryandana, mylza (Jurnal Seni Musik, 2015)
The background of this research is the inappropriate keyboard learning method so it is need an appropriate learning method to solve that problem. The research statement of the problem is how to use Ã¢â‚¬Ëœmusic styleÃ¢â‚¬â„¢ as a medium in keyboard learning to improve studentsÃ¢â‚¬â„¢ activity in keyboard learning process in music extracurricular in the Elementary School 1 Kalipuncang Wetan and how the process of keayboard learning method. This research is done by using classroom action research method which the research is divided into 2 cycles. Each cycle is done with planning, action, observation and reflection. The data collection method is done by doing observation, interview, documentation and assessment. The data analysis techniques in this research are qualitatively and quantitatively. The research results shows that the use of Ã¢â‚¬Ëœmusic styleÃ¢â‚¬â„¢ can improve the studentsÃ¢â‚¬â„¢ activity in keyboard learning activity in music extracurricular. Based on the assessment result in the cycle 1, 50% students can reach the good and very good score (>80) then it is improved in the assessment result of cycle 2, 80% students can reach good and very good score. according to observation result that consist of (1)behavior (2) enthusiasm (3) discipline (4) activity. On the assessment of the cycle 2, 4 aspects are improved and there is no students that get low score.Ã‚Â